“May Be a Picture of a Dog and a Book”: The Inaccessibility of Public Libraries’ Social Media Feeds - Hill, Heather; Oswald, Kevin (Partnership, 2023)
This article investigates the accessibility of Ontario public libraries’ social media feeds. Social media plays an important role in how public libraries engage with their communities. This patron engagement outside of library-maintained websites raises questions around accessibility for persons with disabilities. Given the increasing usage of social media as a communication mechanism, how accessible are Ontario public libraries’ social media feeds? Of specific interest here is the use of alternative (alt) text to describe images in Ontario public libraries’ social media posts. Findings indicate a dearth of alt text in social media feeds. The authors make suggestions for creating good alt text in order to create a more equitable environment.